GLOBAL ISSUES IN GENDER EQUALITY IN WORLD POLITICS - Kholboeva Zarifa Odil kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract There are several issues related with gender equality such as under representation of women in world politics, gender-based violence, economic inequality and discriminatory laws and policies. Different political theories see these issues differently, liberealistic feminism emphasizes individual rights while realistic feminism emphasizes security , power over social issues. Additionally, marxsim links gender oppression to capitalist exploitation while post colonialism shows how imperialism have shaped gender roles. Importantly, radical feminism highlights patriachy as a biggest opposition towards gender equality.